Development of Fluorescent Protein Probes Specific for Parallel DNA and RNA G‐Quadruplexes. Issue 1 (9th December 2015) - Dang, Dung Thanh; Phan, Anh Tuân
Abstract: We have developed fluorescent protein probes specific for parallel G‐quadruplexes by attaching cyan fluorescent protein to the G‐quadruplex‐binding motif of the RNA helicase RHAU. Fluorescent probes containing RHAU peptide fragments of different lengths were constructed, and their binding to G‐quadruplexes was characterized. The selective recognition and discrimination of G‐quadruplex topologies by the fluorescent protein probes was easily detected by the naked eye or by conventional gel imaging. Abstract : Attaching CFP to the G‐quadruplex‐binding motif of the protein RHAU yields a useful fluorescent probe for specific detection of parallel G‐quadruplexes. The selective recognition and discrimination of G‐quadruplex topologies by the fluorescent protein probes were easily detected by the naked eye or by fluorescence imaging.